2018
DOI: 10.3906/bot-1612-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of logistic regression and maximum entropy for distribution modeling of range plant species (a case study in rangelands of western Taftan, southeastern Iran)

Abstract: This study aimed to compare the efficiency of logistic regression and maximum entropy models for distribution modelling of plant species habitats in the rangelands of western Taftan, southeastern Iran. Vegetation cover was sampled using a systematicrandomized method. Soils were sampled at 0-30 and 30-60 cm depths through digging of eight soil profiles. The agreement between predictive maps generated by models with documented maps of habitats indicated that logistic regression was able to predict the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The MaxEnt software (version 3.3.3 k), which is based on the ME approach, is conducted for GWR potential mapping. Groundwater potential mapping 63,64 , flood 30 , landslide 65,66 , rangeland 67,68 , earthquake 69 , species distribution 70 , springs and wells 71 , and groundwater quality 72 .…”
Section: Modelsmentioning
confidence: 99%
“…The MaxEnt software (version 3.3.3 k), which is based on the ME approach, is conducted for GWR potential mapping. Groundwater potential mapping 63,64 , flood 30 , landslide 65,66 , rangeland 67,68 , earthquake 69 , species distribution 70 , springs and wells 71 , and groundwater quality 72 .…”
Section: Modelsmentioning
confidence: 99%
“…For the current model, the jackknife evaluations and percent contributions indicated that geological formation (jeo), soil groups (soil), and elevation (dem) are the main factors influencing the species' current distribution (Figures 5 and 6; Table 1). Edaphic factors are emphasized by many studies for their important contribution to the ENM of plant species (Pir Sahragard and Ajorlo, 2018). Moreover, there are a number of studies that show that altitude affects the distribution of plant species (Maltez-Mouro et al, 2005;Baudraz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The species distribution model was created with the maximum entropy algorithm, Maxent v. 3.3.3 (http:// biodiversityinformatics.amnh.org/open_source/maxent/) (Phillips et al, 2004(Phillips et al, , 2006. This software was chosen because of its successful discrimination performance for presence-only data and small sample sizes (Wisz et al, 2008;Piri Sahragard and Ajorlo, 2018). The Maxent algorithm fundamentally builds species distribution models by quantifying the unknown likelihood distribution, determining the occurrence of a species across a study area without any inferring groundless information about the observed distribution (Salter and Michael, 2012).…”
Section: Spatial Modelingmentioning
confidence: 99%
“…There are some species that migrate toward elevated habitats to reach more suitable conditions for their development (Parmesan & Yohe, 2003). Moreover, variables related to soil characteristics are highlighted by many researchers for their importance in plant species distribution (Piri Sahragard & Ajorlo, 2018). The MaxEnt model predicts the distribution of SAVI and shows differences from the present occurrences.…”
Section: Model Performancementioning
confidence: 99%